(untitled) (Architecture Image Studies, 2025)
The increasing capabilities of generative artificial intelligence (GenAI) to produce outputs resembling human creations have ignited a global debate regarding the adequacy of current copyright law. To effectively navigate the complex landscape of copyright protection for AI-generated works, this paper employs a comparative legal analysis. It examines the divergent approaches adopted by China and Japan. China, notably, has become a pioneer by judicially recognizing copyright for certain AI-generated works, influenced by utilitarian principles aimed at fostering innovation, although questions of ownership between developers and users remain debated. In contrast, Japan maintains a more cautious stance, generally requiring sufficient human creative contribution and viewing AI primarily as a tool. Japanese guidance emphasizes evaluating creative intention and contribution on a case-by-case basis. Vietnam, currently adhering to a traditional copyright philosophy based on human authorship and originality rooted in natural rights theories, presently does not recognize copyright for AI-generated works, finding it challenging under existing legal provisions that exclude mere support or material providers from authorship. Drawing insights from the contrasting experiences of China and Japan, this study identifies shared challenges and potential strategies. Ultimately, the paper offers practical recommendations for Vietnamese policymakers and legal professionals on developing a suitable legal framework that clarifies criteria for human contribution and originality, potentially framing AI as a creative tool, to adapt Vietnamese copyright law to the evolving AI era.